How to win․ The theme of the fight and the image of the warrior in the khachkar figure relief of Artsakh - Petrosyan, Hamlet (History and Culture, 2023)
One of the essential features of the khachkar culture of Artsakh is the figure relief depicting mortals, which has been especially widespread since the 12th century. The Artsakh khachkar figure relief depicts images, themes or scenes that usually have nothing in common with official Christianity, although they are placed next to the cross and accompanied by canonical inscriptions on the Last day. The figure reliefs represent warriors, princes and craftsmen, women and children. They represent the idealized image of the deceased in real life and the expectations of immortality after death. The themes of fight, hunting, feast, inconsolable mourning, “family portrait” and “waiting for a cross” can be distinguished. One of the most common images in the reliefs are horsemen and foot soldiers, who are depicted with weapons, with family members, servants, in the ritual drinking of wine, etc.